On-Ship Trinocular Stereo Vision: An Experimental Study for Long-Range High-Accuracy Localization of Other Vessels - Kotaro Yoshihara; Shigehiro Yamamoto; Takeshi Hashimoto (Journal of Marine Science and Engineering)
Recently, several initiatives regarding maritime autonomous surface ships (MASSs) have been implemented worldwide. One of the fundamental technologies for attaining MASSs is the recognition and localization of surrounding ships. Traditional navigational instruments are inadequate for recognizing objects, and the authors investigated the potential of stereo vision. Conventional stereo camera systems are not suitable for localizing very distant objects. One proposed solution is to use an additional camera, thus using three-camera measurements of objects at long distances to reduce positional measurement errors, incorporating time-series averaging and keypoint-based techniques. This study evaluated experimentally the accuracy of measurements using three ship-mounted cameras. The accuracy and precision of stereo measurements depend on the distance between the camera positions, referred to as the baseline length. Conventional stereo cameras are typically used to measure objects at distances of up to 200 times the baseline length. This study indicates that, using trinocular stereo vision, a target ship at distances up to 2500 m, which is 500 times the baseline length, can be measured with an accuracy of approximately 5% of the RMSE.